The Effect of Work Discipline and Cooperation On Performance Through The Work Environment as a Mediating Variable: Case Study on Samsat Employees of UPT Revenue in Gowa Regency - Pratiwi, Annisa Eka; Sahabuddin, Romansyah; Musa, Muh. Ichwan; Burhanuddin; Natsir, Uhud Darmawan (PT. Maju Malaqbi Makkarana, 2026)
This study analyzes the influence of work discipline and cooperation on employee performance and the role of the work environment as a mediating variable in employees of the Gowa Regency Regional Revenue Unit Samsat. Using a quantitative approach with an associative design, data were collected through questionnaires to 46 respondents and analyzed using SEM-PLS to assess the validity, reliability, and structural relationships between variables. The results of the study show that work discipline and cooperation have a positive effect on the work environment, as well as have a significant direct influence on employee performance. The work environment has also been shown to have a positive effect on performance and mediates the relationship between work discipline and cooperation and performance. These findings confirm that employee performance improves optimally when discipline and cooperation are supported by a conducive work environment